Predictive modelling of surface subsidence above an underground coal mine at Máza-Váralja-South (Northeast Mecsek, Hungary) - Görcs, Noémi Lívia (Hungarian Geographical Bulletin, 2011)
Today the number of the environmental hazards multiplied - mostly due of human impact. The anthropogenic landforms can be predicted by engineering methods in a mining area. These methods became the instruments of Environmental Impact Assessment (EIA). In this paper, such calculation method was applied, but it was combined with GIS. The vertical and horizontal spatial extent of a negative montanogenic landform was modelled. The results of this combined method estimate the locations of the expected major subsidences, thus it would be the basis of monitoring by surveying.